Palm Oil And Pregnancy: A Review of Recent Research - Loso Judijanto (Jurnal Ners, 2026)
Palm oil has become a major dietary fat source in many parts of the world, and increasing attention has been directed toward its potential effects on maternal health and pregnancy outcomes. Nutritional components of palm oil, particularly carotenoids, tocotrienols, and vitamin E, have been hypothesized to influence maternal antioxidant capacity, micronutrient status, and fetal development. This study aimed to systematically review recent research on the role of palm oil during pregnancy and its effects on related health outcomes. A qualitative research design using a Systematic Literature Review (SLR) was applied. Data collection was conducted through the Scopus database. The initial search with the term palm oil AND health yielded 2,183 results. After refining the search to include pregnancy-related terms, 243 articles were identified. Screening criteria were then applied: publication period (2020–2025), language (English), and accessibility (Open access and Open archive). After exclusions, 37 articles met all criteria and were included for final analysis. Data were analyzed through thematic synthesis, categorizing findings into maternal outcomes, oxidative stress modulation, and neonatal health indicators. The results showed that palm oil supplementation, particularly red palm oil, improved maternal vitamin A status, reduced oxidative stress, and showed positive trends in fetal growth and neonatal birth weight. Nonetheless, variability in study design, population characteristics, and supplementation methods indicates the need for cautious interpretation. In conclusion, palm oil has the potential to confer maternal and neonatal health benefits when consumed as part of a balanced diet. Future research should apply longitudinal and standardized clinical approaches to strengthen causal understanding and guide nutritional policy.